Examining the efficiency of mechanic/enzymatic pretreatments in micro/nanofibrillated cellulose production - Tozluoğlu, Ayhan; Poyraz, Bayram; Candan, Zeki (Maderas. Ciencia y Tecnología, 2018)
There is still a need to improve the production sequences of micro fibrillated and nano fibrillated celluloses to obtain more economic and better quality products. The aim of this study was to improve the production efficiency and quality of micro fibrillated and nano fibrillated celluloses by examining the enzyme (xylanase endo-1,4-) employed in pretreatment sequences. Fairly homogeneous nano fibrillated cellulose with a width of 35 ± 12 nm was produced in this study. Sequences employed to produce micro fibrillated and nano fibrillated celluloses decreased the cellulose crystallinity of bleached kraft pulp and lower total crystalline index and lateral order index values were observed for micro fibrillated and nano fibrillated celluloses in FTIR examinations. Lower crystallinities were also defined by 13C-NMR (46.2 ppm), which was substantiated with C6 peaks in the amorphous domain. Sequences to produce micro fibrillated and nano fibrillated celluloses resulted in shorter fiber dimensions with less ordered cellulose structure leading lower thermal degradation that reveal main polymer chain source from cellulose units. Dynamic mechanical thermal analysis results showed that the initial and maximum storage modulus of the nano fibrillated and micro fibrillated celluloses films were improved by 114% and 101%, respectively. The storage modulus of micro fibrillated and nano fibrillated celluloses films were 4.96 GPa and 2.66 GPa at temperature of 235°C, respectively.